Aggregation and Interaction of cationic nanoparticles on bacterial surfaces - Hayden, Steven C.; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2012)
Cationic monolayer-protected gold nanoparticles (AuNPs) with sizes of 6 or 2 nm interact with the cell membranes of Escherichia coli (Gram−) and Bacillus subtilis (Gram+), resulting in the formation of strikingly distinct AuNP surface aggregation patterns or lysis depending upon the size of the AuNPs. The aggregation phenomena were investigated by transmission electron microscopy and UV−vis spectroscopy. Upon proteolytic treatment of the bacteria, the distinct aggregation patterns disappeared.